Bibliometric Analysis using VOSviewer with Publish or Perish of Chinese Speaking Skills Research - Phuangthanasan, Kittithara; Wongsaphan, Montree (ASEAN Journal of Educational Research and Technology, 2024)
The purpose of this research is to analyze research trends regarding Chinese speaking skills using bibliometric analysis methods. Bibliometric analysis methods with VOSviewer were used in this research. The data source was taken from the Google Scholar database in the period 2019 - 2024. The total number of documents found during the last 5 years was 780 documents. The results of the article data that research on was found that the number of publications regarding Chinese speaking skills has increased from 2019-2020. The highest number of papers in 2020 was 228 papers. Then, in 2021 the data decreased every year until 2024. The results of article data mapping produce three forms of visualization, namely network, overlay, and density visualization. The mapping results show that research on statistics still needs to be carried out, especially regarding Chinese speaking skills. This research concluded that the trend of research discussing Chinese speaking skills is decreasing, although, in terms of its use, it is still very important, especially in processing quantitative research data. Lorem Ipsum is simply dummy text of the printing and typesetting industry.